Traumatic Experiences among Offenders: The Need for Trauma-Informed Practice within the Criminal Justice System - Bagdonaitė-Jankauskienė, Sandra; Klimukienė, Virginija (Psichologija, 2025)
Research on traumatic experiences and post-traumatic stress within Lithuanian prisons has been scarcely conducted so far. International studies indicate a significantly higher prevalence of adverse childhood experiences and various mental health difficulties, including post-traumatic stress-related disorders, among the prison population compared to the general population. Furthermore, a connection has been observed between prolonged and repetitive childhood adversity and an increased risk of offending. Thus, existing empirical data support theoretical assumptions that adverse childhood experiences may play a significant etiological role in explaining dynamic risk factors. This, in turn, provides a foundation for the application of trauma-informed practice within the criminal justice system. The primary aim of this article is to highlight the need for trauma-informed practice, to introduce its conceptual framework, and to explore potential avenues for its implementation in the Lithuanian criminal justice system. The article concludes with recommendations grounded in research evidence and international best practice.
Keywords: offenders; traumatic experiences; trauma-informed practice